Increased Procoagulant Activity of Red Blood Cells from Patients with Homozygous Sickle Cell Disease and β-Thalassemia - Helley, Dominique; Eldor, Amiram; Girot, Robert; Ducrocq, Rolande; Guillin, Marie-Claude; Bezeaud, Annie (Thrombosis and Haemostasis, 1996)
It has recently been proved that, in vitro, red blood cells (RBCs) from patients with homozygous β-thalassemia behave as procoagulant cells. The procoagulant activity of β-thalassemia RBCs might be the result of an increased exposure of procoagulant phospholipids (i. e. phosphatidylserine) in the outer leaflet of the membrane. In order to test this hypothesis, we compared the catalytic properties of RBCs of patients with β-thalassemia and homozygous sickle cell disease (SS-RBCs) with that of controls. The catalytic parameters (Km, kcat) of prothrombin activation by factor Xa were determined both in the absence and in the presence of RBCs. The turn-over number (kcat) of the reaction was not modified by normal, SS- or (3-thalassemia RBCs. The Km was lower in the presence of normal RBCs (mean value: 9.1 µM) than in the absence of cells (26 µM). The Km measured in the presence of either SS-RBCs (mean value: 1.6 µM) or β-thalassemia RBCs (mean value: 1.5 pM) was significantly lower compared to normal RBCs (p <0.001). No significant difference was observed between SS-RBCs and p-thalassemia RBCs. Annexin V, a protein with high affinity and specificity for anionic phospholipids, inhibited the procoagulant activity of both SS-RBCs and (3-thalassemia RBCs, in a dose-dependent manner. More than 95% inhibition was achieved at nanomolar concentrations of annexin V. These results indicate that the procoagulant activity of both β-thalassemia RBCs and SS-RBCs may be fully ascribed to an abnormal exposure of phosphatidylserine at the outer surface of the red cells.